Editorial - Van Patten, Elia María (1983)
We come to you again Bulletin Libraries. The work has been arduous, but the support received by people and institutions with whom we worked, we show that was successful. It is appropriate, then transcribe the words of Father Higinio Alas Gomez, Director of the Library "Royo Fernando Linares", Fatima Heredia.